L' importance des plus vieux manuscrits arabes historiques sur papyrus, conservés à Heidelberg, pour l'histoire de la langue arabe et de la culture des premiers siècles islamiques - Khoury, Raif Georges (Quaderni di studi arabi, 1997)
In this paper it is intended to show how important is the question of the investigation on early schools of learning, transmission and writing down the fruit of scientific activities in the two first Islamic centuries. Especially it emphasises the very big importance of the Library of the judge of Egypt, 'Abd Allāh Ibn Lahī'a (97-174/7 15-790), in the process of condification and conservation of an important collection of manuscripts from the first Islamic centuries, from which a certain number is saved on papyrus and is to be found in Heidelberg, in Pairs or in the Vatican Library in Rome. Besides this point of view the present papyri allow to affront with more solidity the problem of the early Islamic culture, in order to put it with more precision in its century and to clarify the problem of its transmission.
Elektronische Reproduktion der Druckausgabe
Gesehen am 23.11.2023